The internationalization of currencies : an appraisal of the Japanese yen - Tavlas, George S.; Ozeki, Yuzuru (Washington, D.C. : International Monetary Fund, 1992)
This working paper assesses the role of the yen as an international currency and also presents a unified theory of international currency use and distinguishes between the roles of a nation as a world banker and as an international financial intermediary.
Includes bibliographical references: p. 51-54.
lje 21/07/2016
Loans
Keywords: Yen, Japanese; Exchange rates; International finance; Monetary policy